Superacid-catalyzed tandem Meyer–Schuster rearrangement/intramolecular hydroamination of o-anilinopropargyl alcohols for the synthesis of 2, 3-dihydro-4(1H)-quinolones. Issue 15 (2nd August 2016) - Sun, Guofeng; Cheng, Fengkai; Tao, Ruiheng; Sun, Yuxing; Pan, Jinpeng; Zhu, Yaohua; Wang, Zhonghua; Wu, Fanhong; Yin, Yan
ABSTRACT: A TfOH-catalyzed synthesis of 2, 3-dihydro-4(1H)-quinolones from o -anilinopropargyl alcohols was developed. Studies of N -protecting groups and substituents in phenyl rings showed that diverse groups could be applied. By controlling the catalyst loading, o -anilinopropargyl alcohols underwent the expected transformation smoothly to produce N -protected or N -deprotected 2, 3-dihydro-4 (1H)-quinolones in good yields. This transformation probably involved a tandem Meyer–Schuster rearrangement/intramolecular hydroamination reaction process. GRAPHICAL ABSTRACT: